2002
DOI: 10.5194/acp-2-249-2002
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of HNO<sub>3</sub> to deliquescent sea-salt particles: a study using the short-lived radioactive isotope tracer <sup>13</sup>N

Abstract: Abstract. The uptake of HNO 3 to deliquescent airborne seasalt particles (RH = 55%, P = 760 torr, T = 300 K) at concentrations from 2 to 575 ppbv is measured in an aerosol flow tube using 13 N as a tracer. Small particles (≈ 70 nm diameter) are used in order to minimize the effect of diffusion in the gas phase on the mass transfer. Below 100 ppbv, an uptake coefficient (γ upt ) of 0.50 ± 0.20 is derived. At higher concentrations, the uptake coefficient decreases along with the consumption of aerosol chloride. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 19 publications
3
82
0
Order By: Relevance
“…The main aim was to investigate the effects of surfactants on the HNO 3 uptake. In the absence of surfactants, the uptake coefficients were consistent with those reported by Guimbaud et al (2002). Offline, ion chromatographic analysis of filter samples confirmed the complete displacement of reacted chloride.…”
Section: Commentssupporting
confidence: 86%
See 1 more Smart Citation
“…The main aim was to investigate the effects of surfactants on the HNO 3 uptake. In the absence of surfactants, the uptake coefficients were consistent with those reported by Guimbaud et al (2002). Offline, ion chromatographic analysis of filter samples confirmed the complete displacement of reacted chloride.…”
Section: Commentssupporting
confidence: 86%
“…From the very high solubility of HNO 3 , the very fast rates for its dissociation in the aqueous phase, and the very fast protonation of chloride, we conclude that solubility, reaction or diffusion cannot limit the rate of uptake of HNO 3 , which was suspected to be responsible for the size and humidity dependence by Saul et al, Liu et al and also earlier by ten Brink (1998). We therefore recommend the bulk accommodation coefficient observed by Guimbaud et al (2002) and Stemmler et al (2008) as a lower limit. With NaCl solution in excess, HNO 3 -protons are nearly completely displaced into the gas phase as HCl at equilibrium due to the divergent behaviour of the activity coefficients of chloride and nitrate at high ionic strength Cl − and RSS (pH ≈ −0.7 to −1, RH 75 %-85 %)…”
Section: Comments On Preferred Valuesmentioning
confidence: 99%
“…The citric acid coating used to trap N 2 O 5 in the denuder system is not able to differentiate N 2 O 5 from HNO 3 . However, any significant presence of HNO 3 formed along the walls upstream of the aerosol flow tube would have been noticed due to its very large wall loss rate coefficient (Guimbaud et al, 2002), which was not observed; the uptake coefficient for labelled N 2 O 5 on the reactor walls calculated from k w was in the range of 10 −7 , which would not lead to substantial HNO 3 production. NO 2 concentrations in the system were measured by switching a NO x analyzer in place of the SMPS system at the beginning of the experiment.…”
Section: Resultsmentioning
confidence: 97%
“…This synthesis route to HNO 3 is well established and HNO 3 yields of up to 90% can be reached at higher humidity [12]. This approach has been used as HNO 3 source in a number of earlier experiments [21,22]. The level of HNO 3 drops rapidly to below 20% with increasing concentration of CO in the reactor and, simultaneously, the HNO 4 share increases from below 5 to over 30%.…”
Section: Resultsmentioning
confidence: 97%